Chemical Composition and Biological Effects of Pistacia atlantica Desf. Oleoresin Essential Oil - Azam Elyasi Ghahfarrokhi; Mina Saeedi; Mahnaz Khanavi*; Somayeh Mojtabavi; Farzad Kobarfard; Mohammad Ali Faramarzi (Iranian Society of Pharmacognosy, 2022)
Background and objectives: The oleoresin of Pistacia atlantica Desf. (known as "Baneh" in Iran) has been frequently used in traditional medicine for its medicinal properties. Herein, P. atlantica essential oil was investigated for its antimicrobial and α-glucosidase inhibitory activities since α-pinene which has been identified as the most abundant component in Pistacia genus oil, has demonstrated antimicrobial and anti-α-glucosidase properties. Methods: Fresh oleoresin was collected from Javanroud, Kermanshah, Iran and the essential oil was obtained by Clevenger-type apparatus. The chemical composition of essential oil was identified with GC/MS analysis and compared with those reported from various regions. The antimicrobial activity was evaluated against various strains (Pseudomonas aeruginosa, Staphylococcus aureus, Escherichia coli, Candida albicans, Saccharomyces cerevisiae, and Lactobacilli spp.) through MIC method. Also, its anti-α-glucosidase property and antioxidant activity by DPPH assay were investigated. Results: GC/MS analysis of the essential oil confirmed the presence of nineteen compounds and among them, α-pinene (64.8%) was identified as the major constituent. Also, β-pinene (5.7%) and cis-limonene oxide (4.5%) were relatively abundant. Our results revealed antimicrobial properties of the "Baneh" essential oil against various bacterial and fungal strains. Moreover, it demonstrated inhibitory activity toward α-glucosidase with IC50 value of 41.5 ± 2.5 mg/mL compared with acarbose (IC50=0.5±0.2 mg/mL). DPPH free-radical scavenging activity assay showed antioxidant activity with IC50 value of 155.2 ± 1.4 mg/mL compared with quercetin (IC50=250.0±0.0 μg/mL). Conclusion: Pistacia atlantica oleoresin essential oil depicted satisfactory antimicrobial activity against both Gram-positive and Gram-negative strains. However, it demonstrated low antioxidant and α-glucosidase inhibitory effects.